P1_8 Turbulence, Atherosclerosis and the Carotid Bruit - Boadle, Roisin; Wigfield, Emma; Dulay, Amanjit Singh (Physics Special Topics, 2009)
<!–[if gte mso 9]> Normal 0 false false false EN-GB X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0; @font-face font-family:Calibri; panose-1:2 15 5 2 2 2 4 3 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-1610611985 1073750139 0 0 159 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman"; mso-fareast-language:EN-US; .MsoChpDefault mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; @page Section1 size:612.0pt 792.0pt; margin:72.0pt 72.0pt 72.0pt 72.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> This article discusses turbulence in the human carotid artery, its links to narrowing of the artery due to atherosclerosis and the amplitude of the carotid bruit. The Reynolds number at the narrowest part of the artery is found as a function of the degree of stenosis which is then related to the amplitude of the carotid bruit. It is demonstrated that the amplitude of the bruit could be used as an estimate of the degree of stenosis of the artery.